Automated, robotic dry-cleaning of solar panels in Thuwal, Saudi Arabia using a silicone rubber brush. (1st September 2018) - Parrott, Brian; Carrasco Zanini, Pablo; Shehri, Ali; Kotsovos, Konstantinos; Gereige, Issam
Graphical abstract: Highlights: Robotic dry-cleaning improved the performance of a PV system by ∼0.25% per day. The tested robotic system did not damage the panels in any measurable way. The previously reported silicone foam brush proved successful during deployment. Abstract: The challenge of mitigating power loss in solar photovoltaic (PV) systems—due to dust—is critical to the economical deployment of solar in arid regions. These areas suffer from high aerosol concentration levels and frequent sand storms that lead to an accumulation of a layer of dust on the surface of solar arrays. The dust stays in place due to only slight and occasional rain fall. This paper presents the results from a study conducted on the effectiveness of dry cleaning solar panels, using an automated robotic cleaning system. The robotic cleaning system is part of a research program related to robotic dust mitigation technologies for solar panels, and includes a new type of brush, which uses silicone rubber foam flaps mounted onto an aluminum core. The study found that the robotic system, using this silicone rubber foam brush, was able to effectively minimize the impact of dust on the solar panels' power output, providing an increase in power output versus the weekly-cleaned controls. This new brush shows promise for use in solar panel dust mitigation due to its effective cleaning performance and low cost, and does not induce any damage to the surface of the solar panels.